ON THE NEED FOR SATELLITE MONITORING OF TRANSBOUNDARY WATERS OF RUSSIA - A. G. Kostianoy; S. A. Lebedev; A. V. Semenov (Проблемы постсоветского пространства)
The article provides information on transboundary watercourses and international lakes of the Russian Federation. We discuss the goals and objectives of environmental monitoring. Particular attention is given to the possibilities of satellite monitoring of transboundary water bodies of the Russian Federation.